Somatic embryogenesis from leaf and shoot tip explants of Jatropha curcas L. - Medipally, Srikanth Reddy; Naresh, Baja; Kumar, S. Manoj; Md. Yusoff, Fatimah; Prathibha Devi, (Indian Society for Education and Environment, 2014)
Jatropha curcas is a non-edible oil plant species and belongs to Euphorbiaceae family. It is gaining the importance as potential renewable feed-stock for biodiesel production. Here in the present study we developed an efficient micropropagation protocol through somatic embryogenesis from leaf and shoot tip explants of Jatropha curcas. Murashigae-Skoog medium supplemented with 2, 4-D (0.5mg/l) and benzylaminopurine (5mg/l) resulted in the production of green embryogenic callus with clearly differentiated somatic embryos with a frequency of plant conversion rate from shoot tip and leaf explants was 51 ± 0.9 and 54 ± 0.6 respectively. The regenerated shoots were rooted on root induction medium, transplanted to pots and later transferred to field. The survival percentage of the transplanted plants was 33±0.1 for shoot tip and 24±0.7 for leaf explant. Therefore, this protocol could be useful for micropropagation of Jatropha curcas as effective feed-stock towards biodiesel production.